(untitled) (Proceedings of Faculty of Civil Engineering, 2025)
This paper presents a practical example for the design of a reinforced-concrete (RC) T-section retaining wall and a T-section seawall in accordance with Eurocode 7 (EC7). The objectives are: a) in the context of Design Approach 3 (DA3), which is applied in Croatia, examine the sensitivity of stability verifications with respect to different classifications of structural and geotechnical actions and to where the corresponding partial factors are applied, and b) to compare the stability of retaining and seawalls of identical geometry. After a brief overview of EC7 and DA3, design calculations are carried out for an RC T-wall under several alternative definitions of actions, and the results of the sliding, overturning, and foundation bearing capacity checks are compared. Finally, the obtained utilization ratios for the retaining and seawall T-walls are compared to highlight the influence of seawater actions (hydrostatic pressure and uplift) on the design.